Effects of tool rake angle and workpiece surface roughness on nanocutting of cu investigated using Multiscale simulation. Issue 12 (13th August 2021) - Wu, Cheng-Da; Fang, Te-Hua; Wei, Yu-Cheng
ABSTRACT: The effects of tool rake angle and workpiece surface roughness on the cutting mechanism and mechanics of Cu are studied using quasi-continuum simulations. These effects are investigated in terms of atomic trajectories, stress distribution, cutting force, resistance factor, and cutting ratio. The simulation results show that negative rake angles lead to a larger cutting force, lower resistance coefficient, and higher cutting ratio than those obtained with positive rake angles. For tools with an initial rake angle of 2° to 8°, the rake angle becomes negative during the cutting process due to the strong adhesion interaction between the tool rake face and chips. The resistance coefficient decreases with increasing tool rake angle for rake angles in the range of 2° to 8°. Tools with negative rake angles of −2° to −8° have similar cutting ratios. The cutting ratio decreases and cutting force increases with increasing surface roughness of the workpiece.